A comparison between flat-plate and evacuated tube solar collectors in terms of energy and exergy analysis by using nanofluid. (5th March 2021) - Eltaweel, Mahmoud; Abdel-Rehim, Ahmed A.; Attia, Ahmed A.A.
Highlights: Nanofluid flow in two stationary solar collectors were investigated. First and second law efficiencies enhance with concentration rise. Nanofluids have higher effect on evacuated tube collector than flat-plate collector. The overall heat loss coefficient is affected by the concentration of nanofluid. Abstract: The continuous increase in energy demand is a challenge for the human future. During the last century, researchers have been concerned with finding efficient methods to generate energy from renewable sources, especially solar energy. Evacuated tube and flat-plate solar collectors are simple, inexpensive systems for domestic applications. The replacement of the working fluid with nanofluid can enhance the heat transfer even for low-temperature applications. There are many comparisons between both collectors in the literature, which indicated that there are different behaviours based on the working conditions; however, the two types of collectors can behave differently if a nanofluid became the working fluid under different working conditions of temperatures, radiation, mass flux rate, and nanomaterial concentration. However, it was observed that there is a lack of publications that cover the comparison between stationary collectors in case of using nanofluids. The present work introduces an extensive experimental study to fill this gap and examine, compare and evaluate the performance of both collectors in terms of energy and exergy efficiencies with and without Multi-walled Carbon Nanotubes/water nanofluid at different mass flux rates. The highest average energy efficiency values achieved with 0.05 wt% Multi-walled Carbon Nanotubes/water nanofluid were 55% and 59% while the highest average exergy efficiency values achieved were 10% and 11.5% for both evacuated tube and flat-plate collector respectively. The overall heat loss coefficient decreased with the increase of the concentration. It was found that 0.020 kg/s m 2 is a critical mass flux rate, and the behaviour of the system changed afterward.